2016
DOI: 10.1097/mao.0000000000001192
|View full text |Cite
|
Sign up to set email alerts
|

Role of STAT1 and Oxidative Stress in Gentamicin-Induced Hair Cell Death in Organ of Corti

Abstract: Rationale Oxidative stress plays a critical role in gentamicin-induced hair cell death. Prior work has implicated the cytoplasmic transcription factor STAT1 as a potential mediator of drug-induced ototoxicity, but role in aminoglycosides is largely unknown. This study investigated aminoglycosides-induced cell death, exploring contributions of reactive oxygen species and STAT1 pathway in injury and protection. Methods Neonatal murine organ of Corti explants from 2-3 day postnatal pups (n=96) were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…In DM with poor metabolic control, the hyperglycaemia and advanced glycation end‐products are strongly conducive to the development of oxidative stress and mitochondrial dysfunction, often culminating in disease complications resulting in organ or system dysfunction . Similarly, oxidative stress and mitochondrial dysfunction have also been shown to be responsible for toxicities incurred by isoniazid, pyrazinamide, aminoglycosides and fluoroquinolones in different experimental models . Due to the shared pathogenetic mechanisms in organ injury, pertaining to poorly managed DM and toxicities incurred by anti‐tuberculosis drugs, the aftermath could be seriously amplified in terms of morbidity and even mortality .…”
Section: Does Oxidative Stress Impact the Outcomes Of Tb In Older Peomentioning
confidence: 99%
See 1 more Smart Citation
“…In DM with poor metabolic control, the hyperglycaemia and advanced glycation end‐products are strongly conducive to the development of oxidative stress and mitochondrial dysfunction, often culminating in disease complications resulting in organ or system dysfunction . Similarly, oxidative stress and mitochondrial dysfunction have also been shown to be responsible for toxicities incurred by isoniazid, pyrazinamide, aminoglycosides and fluoroquinolones in different experimental models . Due to the shared pathogenetic mechanisms in organ injury, pertaining to poorly managed DM and toxicities incurred by anti‐tuberculosis drugs, the aftermath could be seriously amplified in terms of morbidity and even mortality .…”
Section: Does Oxidative Stress Impact the Outcomes Of Tb In Older Peomentioning
confidence: 99%
“…62 Similarly, oxidative stress and mitochondrial dysfunction have also been shown to be responsible for toxicities incurred by isoniazid, pyrazinamide, aminoglycosides and fluoroquinolones in different experimental models. [63][64][65][66] Due to the shared pathogenetic mechanisms in organ injury, pertaining to poorly managed DM and toxicities incurred by anti-tuberculosis drugs, the aftermath could be seriously amplified in terms of morbidity and even mortality. 67 In the geriatric population, as oxidative stress and mitochondrial dysfunction are also underscored mechanisms of the ageing process, with chronic inflammation as the pathogenetic basis in many 'degenerative' disorders, quite like DM, it would be reasonable to anticipate a similar interacting scenario resulting in antituberculosis drug toxicities among the geriatric patients.…”
Section: Does Oxidative Stress Impact the Outcomes Of Tb In Older Peomentioning
confidence: 99%
“…Many studies, including our previous studies, have shown that caspase-associated apoptosis plays an important role in aminoglycoside-induced ototoxicity (Guan et al, 2016;He et al, 2017). The accumulation of ROS in the lysosomes and mitochondria of HCs leads to the upregulation of caspase genes, which further induces apoptosis of HCs (Esterberg et al, 2016;Jiang et al, 2016;Guo et al, 2019). In the central nervous system, myosin contraction plays an important role in oxidative stress-related neuronal apoptosis, myosin contraction, and the formation of relevant complexes needed to activate the expression of caspase-3 through the ROCK1-related pathway, indicating positive feedback regulation between myosin contraction and the oxidative stressinduced apoptosis pathway (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…Ototoxic deafness is severe and permanent hearing loss and/or vestibular dysfunction caused by ototoxic drugs, such as aminoglycoside antibiotics, loop diuretics, antimalarials and platinum chemotherapy ( Layman et al., 2015 , Landier, 2016 ; Lin et al, 2015 ). Accumulating evidence have suggested that the aminoglycoside antibiotics-induced ototoxicity is associated with the generation of reactive oxygen species (ROS) and nuclear factor-κB (Nf-κB) misregulation in outer hair cells ( Jiang et al., 2016 , Kamogashira et al., 2015 , Layman et al., 2015 ). Ototoxic functional impairment and cellular degeneration are involved in activated non-classic apoptotic and necrotic pathways ( Fernández-Cervilla et al., 2017 , Jiang et al., 2006 ).…”
Section: Expression and Function Of Hdacs In Hearing Lossmentioning
confidence: 99%